(untitled) (Lapai Journal of Economics, 2021)
The study has examined the patterns and determinants of Public Expenditure and revenues in Nasarawa State where it focuses on the statutory allocations received by the State government from the consolidated revenue accounts of the federation, the value added tax (VAT) proceeds and the internally generated revenues (IGR) on the one hand vis-a-vis the total expenditure disbursements of the State. The study employed regression analysis. The study subjected the annual budget estimate of Nasarawa State government (1997-2004) to a thorough scrutiny. The study discovered that the State government is over-dependent on the oil monies coming into the State from the consolidated revenue accounts of the federation and the value added tax proceeds in order to execute both its capital as well as the recurrent programmes. This study therefore recommends an over-haul in the entire processes of revenue collection by diversifying its internal revenue base in order to reduce the over-depended on the reven ues from the federation account. Also, the state government should revolutionize in solid minerals development, and hasten the development of it’s tourism potentials.